Advances in Downy Mildew Research
DOI: 10.1007/0-306-47914-1_1
|View full text |Cite
|
Sign up to set email alerts
|

Towards and Understanding of the Evolution of the Downy Mildews

Abstract: PeronosporalesObligate parasites of dicotyledons (very rarely monocotyledons). Thallus mycelial and intercellular with haustoria; zoosporogenesis, when present, by internal cleavage, otherwise asexual reproduction by deciduous conidiosporangia; conidiosporangiophores well-differentiated, persistent; oogonia thin-walled, oospore single, aplerotic with a well-defined exospore wall layer derived from persistent periplasm. Possibility that all are dependent on exogenous sources of sterols. Peronosporaceae: Mycelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 146 publications
0
27
0
Order By: Relevance
“…Bhattacharya et al [17] suggested a mean age for the split between Oomycetes and Bacillariophyta of 936 Ma (range: 1150 -770 Ma). Internal calibration of the Oomycetes molecular phylogeny has not yet been attempted, but Dick [1,18] presented a compelling case for a comparatively recent (Cenozoic Era) radiation of the phylogenetically derived Peronosporales (Downy Mildews). Fossil evidence prior to the Cretaceous Period is rare, and where fossils have been documented their affinities are difficult to establish [19].…”
Section: Introductionmentioning
confidence: 99%
“…Bhattacharya et al [17] suggested a mean age for the split between Oomycetes and Bacillariophyta of 936 Ma (range: 1150 -770 Ma). Internal calibration of the Oomycetes molecular phylogeny has not yet been attempted, but Dick [1,18] presented a compelling case for a comparatively recent (Cenozoic Era) radiation of the phylogenetically derived Peronosporales (Downy Mildews). Fossil evidence prior to the Cretaceous Period is rare, and where fossils have been documented their affinities are difficult to establish [19].…”
Section: Introductionmentioning
confidence: 99%
“…It should be remembered, however, that downy mildews do not always form haustoria (Fraymouth, 1956), and their intercellular hyphae also provide an interface for nutrient uptake and general inter-communication, as in other non-haustorial biotrophs (Spencer-Phillips, 1997). Indeed Dick (2002a) has pointed out that the development of haustoria may have evolved separately even within the oomycetes, so that haustoria may have a different physiology and function in each of the genera Albugo, Peronospora and Sclerospora.…”
Section: Introductionmentioning
confidence: 95%
“…Downy mildews are oomycetes belonging to the orders Peronosporales and Sclerosporales in the class Peronosporomycetes, within the kingdom Straminipila, according to Dick (2002aDick ( , 2002b. The taxonomy of this group of organisms, however, is under continuous revision.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations